Limb-girdle Muscular Dystrophy Type 2A with Mutation in CAPN3: The First Report in Taiwan - Chien-Hua Wang; Wen-Chen Liang; Narihiro Minami; Ichizo Nishino; Yuh-Jyh Jong (Pediatrics and Neonatology)
The autosomal recessive limb-girdle muscular dystrophy type 2A (LGMD2A) is caused by mutations in the calpain 3 (CAPN3) gene, and it is characterized by selective atrophy and weakness of proximal limb and girdle muscles. We report a 33-year-old woman with initial presentations of exercise intolerance and running difficulty at age 15 years. At presentation, waddling gait, positive Gowers' sign, and marked muscle atrophy in pelvic and leg muscles were noted. Muscle computed tomography (CT) imaging demonstrated symmetric involvement of the posterior thigh muscles with relative sparing of vastus lateralis, sartorius, and gracilis. Muscle biopsy revealed a dystrophic change and many lobulated fibers on NADH-tetrazolium reductase staining. Genetic analysis of the CAPN3 gene identified a novel homozygous mutation of c2047_2050 del4, p.Lys683fs mutation, confirming the first LGMD2A patient in Taiwan.